Legal Consequences For Investors In A Public Limited Liability Company That Applies Multiple Voting Sharing System - Larasati Anyufa; Lastuti Abubakar; Pupung Faisal (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
The Indonesian capital market has undergone changes, especially related to legal reforms that can be seen in terms of quantity including legal certainty and protection for investors. These changes are accompanied by the application of the new economy encouraged by the Government of Indonesia, especially for the development of digital technology because technology companies and start-ups have the opportunity to invest or do business in Indonesia. One form of encouragement for Indonesia's new economy is the issuance of Financial Services Authority Regulation Number 22 / POJK.04 / 2021 concerning the Application of Share Classification with Multiple Voting Rights by Issuers with Innovation and High Growth Rates Conducting Public Offerings of Equity Securities. The application of dual class shares in the multiple voting shares system is expected to provide protection for the company's vision and mission so that it can develop properly. The research method used is normative juridical by collecting secondary data related to research problems.